IMPLEMENTASI ETIKA AKUNTANSI SYARIAH DALAM PENGELOLAAN TUNJANGAN PNS DAN PPPK DI DINAS PENDIDIDKAN DAN KEBUDAYAAN KABUPATEN TEGAL - lizatul zakiyah; Fatkhuri Fatkhuri (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the implementation of Islamic accounting ethics in the management of benefits for Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) at the Tegal Regency Education and Culture Office. The research approach used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study indicate that the management of benefits has been implemented based on the principles of accountability, transparency, and fairness, and is in line with the ethical values ​​of Islamic accounting, namely trustworthiness, honesty (mas'uliyah), and justice (al adl). However, there are still limitations in the apparatus' understanding of the concept of Islamic accounting ethics conceptually. This study is expected to provide theoretical contributions to the development of public sector Islamic accounting studies as well as practical contributions to improving the quality of benefits management based on Islamic values.